Feasibility of a Study Within a Trial to evaluate a decision support intervention for families deciding about research on behalf of adults lacking capacity to consent (CONSULT SWAT) - Shepherd, Victoria; Smallman, Kim; Wood, Fiona; Gillies, Katie; Martin, Adam; Moore, Maria; Todd, Stacy; Hood, Kerenza (Current controlled trials in cardiovascular medicine, 2025)
Background Trials involving adults who lack capacity to consent can be challenging, partly due to the involvement of ‘proxy’ decision-makers. This is usually a family member, who advises the researchers about the person’s wishes. Families can find decision making difficult and some experience a decisional burden. Following the development of a decision aid for family members making trial participation decisions, we are conducting a mixed-methods randomised Study Within a Trial (SWAT) to evaluate its (cost-)effectiveness. This paper reports the feasibility stage conducted in one host study to inform delivery of the main SWAT. Methods Family members approached to act as a consultee for the host study were randomised 1:1 to receive the decision aid booklet alongside standard study information (intervention), or standard information plus a blank notebook (control), and asked to complete the CONCORD scale (Combined Scale for Proxy Informed Consent Decisions) questions about their experience and take part in a semi-structured interview. Acceptability of the SWAT was assessed through exploring recruitment rates and data completeness, and qualitatively through interviews with family members and research staff. Interviews were analysed using a rapid qualitative approach. Results In total, 92 family members were randomised to the SWAT and 16 completed the CONCORD questionnaire. Interviews were conducted with consultees ( n = 4), and host study staff ( n = 3) who also provided resource use data. Differences in time staff spent with consultees were small. Key themes included (1) setting up the SWAT and balancing priorities with the host study, (2) differences when recruiting consultees to a SWAT, (3) feasibility and acceptability of the SWAT, (4) challenges of measuring decision quality and (5) views and experiences of the decision support intervention. Conclusion The CONSULT SWAT is feasible, but changes to study processes are needed in advance of the main SWAT. The findings suggest that attempting to seamlessly integrate the SWAT into the host study may have inadvertently led to it becoming ‘invisible’ to consultees. The small number of trials involving participants lacking capacity limits opportunities for developing the evidence-base. Recruitment of host trials continues, with a focus on evaluating the intervention in a broad range of populations and settings. Trial registration The SWAT is registered as SWAT #159 with the Northern Ireland Hub for Trials Methodology Research SWAT repository (registered 09.08.2020).